ABS (Acrylonitrile Butadiene Styrene) composition and preparation method and application thereof
By regulating the butadiene content in ABS resin combined with PETG copolyester and combining it with flame retardant, the problem of bromine flame retardant ABS resin burning and yellowing during laser marking is solved, and the mechanics of ABS composition is improved Performance and flame retardant properties achieve good marking effect and toughness.
Patent Information
- Application Number
- CN202411542812.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing bromine flame-retardant ABS resin is prone to burning and yellowing during laser marking, resulting in blurred marking, making it difficult to take into account both flame retardant performance, laser marking effect and mechanical properties.
By regulating the combination of butadiene content in ABS resin with PETG copolyester, and combining bromine and antimony flame retardants, the transmission effect of PETG copolyester and the promotion of carbonization by absorbing laser energy is improved, laser operation is improved Standard effect and improve mechanical properties.
It effectively improves the problem of laser marking and yellowing of bromine flame retardant ABS, and at the same time improves the mechanical properties of the ABS composition, achieving good flame retardant performance, marking effect and toughness.
Smart Images

Figure BDA0005113156720000051 
Figure BDA0005113156720000052 
Figure BDA0005113156720000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer compound compositions, and in particular to an ABS composition and a preparation method and application thereof. Background Art
[0002] ABS resin is an amorphous polymer made of three monomers: acrylonitrile, butadiene, and styrene. Acrylonitrile provides ABS resin with resistance to chemical solvents and heat resistance, butadiene gives ABS resin good toughness and impact resistance, and styrene makes ABS resin have excellent rigidity and processing performance; these excellent properties make ABS resin a preferred choice for structural component applications. However, ABS resin itself is a flammable material and it is difficult to meet the application needs of industries with high safety regulations. Therefore, ABS resin needs to be modified to enhance its flame retardant properties.
[0003] At present, ABS resin is mainly modified by adding flame retardants. Among them, the bromine flame retardant ABS formed by the halogen-antimony compound flame retardant of bromine flame retardant and antimony oxide and ABS resin has better comprehensive performance and is widely used in household appliances or electronic and electrical shell products (such as relay shells, capacitor shells, low-voltage electrical appliances, plug connectors, etc.). This type of shell product usually needs to be marked by laser engraving (i.e. laser marking). In actual industrial production, infrared laser engraving with a wavelength of 1064nm is mostly used. This method uses the thermal effect of the laser to quickly carbonize, foam or discolor the surface of the object, thereby obtaining a mark different from the color of the base.
[0004] In actual application, it is found that during the laser marking process, the shell products made of bromine flame retardant ABS are prone to serious burnt yellowing, blurred fonts and other problems on the surface of the shell products, which seriously affects the marking effect. In the prior art, laser marking agents or improved flame retardants are generally added to improve the marking effect of bromine flame retardant ABS products. For example, patent CN118048011A discloses an ABS composite material and its application. By adding more inorganic components (silicates and flame retardant synergists) to replace conventional antimony white, the ABS composite material has better flame retardant properties and laser marking effects, but it also causes the toughness of the ABS composite material to decrease, that is, it is difficult to have good flame retardant properties, laser marking effects and mechanical properties. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide an ABS composition and a preparation method and application thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides an ABS composition, comprising the following components in parts by weight:
[0008] ABS resin 53-73 parts, PETG copolyester 15-30 parts, brominated flame retardant 11-13 parts, antimony flame retardant 1-3 parts;
[0009] The weight percentage of butadiene in the ABS resin is ≥20%, and the weight percentage of 1,4-cyclohexanedimethanol in the PETG copolyester is 10% to 30%;
[0010] The PETG copolyester adopts ISO 1133-1:2011 standard, and the melt mass flow rate at 220° C. and 10 kg is ≥18 g / 10 min.
[0011] The present invention adjusts the content of butadiene in ABS resin, combines it with a specific PETG copolyester, and simultaneously adds a bromine-based flame retardant and an antimony-based flame retardant, and utilizes the penetration effect of PETG copolyester on marking light waves (reducing the absorption of laser waves by the ABS composition) and the carbonization promoting effect of PETG copolyester in the process of ABS absorbing laser energy, so that the PETG copolyester and the ABS resin interact with each other in the laser marking process, thereby effectively improving the yellowing problem of bromine-based flame-retardant ABS laser marking and greatly improving the mechanical properties of the ABS composition.
[0012] Optionally, the weight proportion of ABS resin in the above-mentioned ABS composition can be 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, and 72 parts, the weight proportion of PETG copolyester can be 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, and 28 parts, the weight proportion of bromine-based flame retardant can be 11.5 parts, 12 parts, and 12.5 parts, and the weight proportion of antimony-based flame retardant can be 1.5 parts, 2 parts, and 2.5 parts.
[0013] The weight percentage of ABS resin in the ABS composition of the present invention is greater than or equal to 50%; the weight percentage of butadiene in the ABS resin is preferably 20% to 35%, specifically 21%, 22%, 23%, 24%, 24%, 25%, 26%, 27%, 28%, 29%, 30%; the weight percentage of butadiene in the ABS resin can be determined by nuclear magnetic resonance, for details, refer to the Chinese document "Nuclear Magnetic Resonance Study of ABS Resin and Effect of Monomer Content on Macroscopic Properties".
[0014] PETG copolyester is polyethylene terephthalate-1,4-cyclohexanedimethanol ester, and the weight percentage of 1,4-cyclohexanedimethanol in PETG copolyester can be specifically 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%; the weight percentage of 1,4-cyclohexanedimethanol in PETG copolyester can be determined by infrared absorption spectroscopy (IR) combined with nuclear magnetic resonance (NMR), and specific reference can be made to Chinese patent CN104569022B (a method for analyzing the content of 1,4-cyclohexanedimethanol units on a copolyester molecular chain).
[0015] Optionally, the melt mass flow rate of PETG copolyester can specifically be 22 g / 10 min, 24 g / 10 min, 26 g / 10 min, 28 g / 10 min, 30 g / 10 min, 32 g / 10 min, 34 g / 10 min, 36 g / 10 min, 38 g / 10 min.
[0016] As a preferred embodiment of the ABS composition of the present invention, among the components of the ABS composition, the weight proportion of ABS resin is 57 to 65 parts, and the weight proportion of PETG copolyester is 20 to 25 parts.
[0017] As a preferred embodiment of the ABS composition of the present invention, the weight percentage of butadiene in the ABS resin is 22% to 29%.
[0018] As a preferred embodiment of the ABS composition of the present invention, the melt mass flow rate of the PETG copolyester is 20 to 40 g / 10 min.
[0019] As a preferred embodiment of the ABS composition of the present invention, the components of the ABS composition further include 0.5 to 1 parts by weight of a processing aid.
[0020] Optionally, the processing aid includes at least one of an anti-dripping agent, an antioxidant, and a lubricant; specifically, the anti-dripping agent can be at least one of SAN-coated polytetrafluoroethylene micropowder, acrylate-coated polytetrafluoroethylene micropowder, and siloxane-coated polytetrafluoroethylene micropowder; the antioxidant can be at least one of a hindered phenol antioxidant and a phosphite antioxidant; the lubricant can be at least one of amides, stearates, esters, and silicones.
[0021] As a preferred embodiment of the ABS composition of the present invention, the bromine-based flame retardant includes at least one of bromotriazine and brominated epoxy; and / or the antimony-based flame retardant includes at least one of antimony oxide and antimonate. Specifically, the antimony oxide is antimony trioxide, and the antimonate is sodium antimonate.
[0022] In a second aspect, the present invention provides a method for preparing the above-mentioned ABS composition, comprising the following steps: mixing the components uniformly and then melt-extruding to obtain the ABS composition.
[0023] Specifically, in the above preparation method, a twin-screw extruder can be used for melt extrusion, the temperature of the melt extrusion is 160-210° C., and the screw speed of the twin-screw extruder is 400-600 rpm.
[0024] In a third aspect, the present invention provides the use of the above ABS composition in preparing a plastic housing of a household appliance or an electronic and electrical product. Specifically, the electronic and electrical product may be a relay, a capacitor, a low-voltage electrical appliance, a plug connector, and the like.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention adjusts the content of butadiene in ABS resin, combines it with a specific PETG copolyester, and simultaneously adds a bromine-based flame retardant and an antimony-based flame retardant, and utilizes the penetration effect of PETG copolyester on marking light waves and its carbonization-promoting effect in the process of ABS absorbing laser energy, so that the PETG copolyester and the ABS resin interact with each other in the laser marking process, thereby effectively improving the yellowing problem of bromine-based flame-retardant ABS laser marking and greatly improving the mechanical properties of the ABS composition. DETAILED DESCRIPTION
[0027] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0028] Unless otherwise specified, other materials, reagents, etc. used in the examples and comparative examples can be obtained from commercial sources.
[0029] 1. Raw materials and reagents
[0030] ABS resin 1: The weight percentage of butadiene in ABS resin is 29%, the brand is ABS PA-747S, and the manufacturer is Chi Mei from Taiwan, China;
[0031] ABS resin 2: The weight percentage of butadiene in ABS resin is 25%, the brand is ABSDG-MG29, and the manufacturer is Trinseo;
[0032] ABS resin 3: The weight percentage of butadiene in ABS resin is 22%, the brand is ABSD-120A, and the manufacturer is Guoqiao, Taiwan, China;
[0033] ABS resin 4: The weight percentage of butadiene in ABS resin is 16%, the brand is ABS GP-22, and the manufacturer is INEOS Styrolution;
[0034] PETG resin 1: The weight percentage of CHDM in the PETG resin is 20%, the melt mass flow rate is 22 g / 10 min, the brand is PETG K2012, and the manufacturer is SK Chemical;
[0035] PETG resin 2: The weight percentage of CHDM in the PETG resin is 30%, the melt mass flow rate is 40g / 10min, the brand is PETG PN300, and the manufacturer is SK Chemical;
[0036] PETG resin 3: The weight percentage of CHDM in the PETG resin is 10%, the melt mass flow rate is 20g / 10min, the brand is PETG WS-501, and the manufacturer is Huahong Chemical Fiber;
[0037] PETG resin 4: The weight percentage of CHDM in the PETG resin is 20%, the melt mass flow rate is 12 g / 10 min, the brand is PETG 5083, and the manufacturer is China Resources Chemical;
[0038] PETG resin 5: The weight percentage of CHDM in the PETG resin is 0%, the melt mass flow rate is 28 g / 10 min, the brand is PETG 5511, and the manufacturer is China Resources Chemical;
[0039] PETG resin 6: The weight percentage of CHDM in the PETG resin is 40%, the melt mass flow rate is 25g / 10min, the brand is JN200, and the manufacturer is SK Chemical;
[0040] Bromotriazine: brand name is FR-245, the manufacturer is Dead Sea Bromine of Israel;
[0041] Brominated epoxy: brand name is CXB-714C, manufacturer is Yujin, South Korea;
[0042] Antimony trioxide and sodium antimonate were purchased from Xikuangshan Shanxing Antimony Industry Co., Ltd.;
[0043] The processing aid is prepared by compounding an anti-dripping agent, a lubricant and an antioxidant in a mass ratio of 2:1:1, wherein the anti-dripping agent is POLY TS 30A and the manufacturer is PIC of South Korea; the lubricant is pentaerythritol stearate, and the antioxidant is prepared by compounding a primary antioxidant (THANOX 1010) and an auxiliary antioxidant (THANOX 168) in a mass ratio of 3:2, and pentaerythritol stearate, THANOX 1010 and THANOX 168 are all commercially available.
[0044] 2. Preparation method of ABS composition of the present invention
[0045] According to the formula, the components are mixed evenly and then added into a twin-screw extruder for melt extrusion to obtain an ABS composition; wherein the melt extrusion temperature is 160-210° C., and the screw speed of the twin-screw extruder is 400-600 rpm.
[0046] Table 1 Weight parts of each component of the ABS composition in Examples 1 to 12
[0047]
[0048] Table 2 Weight parts of each component of the ABS composition in Comparative Examples 1 to 6
[0049]
[0050]
[0051] 3. Performance testing
[0052] The ABS compositions in the above-mentioned Examples 1 to 12 and Comparative Examples 1 to 6 were placed in a blast oven, dried at 80° C. for 4 hours, and then injection molded into standard test specimens required for testing using a plastic injection molding machine, with the injection molding temperature being 200 to 220° C. The standard test specimens obtained by injection molding were placed at a relative humidity of 50% and a temperature of 23° C. for at least 24 hours to conduct different performance tests, and the test results are shown in Table 3.
[0053] The specific test method is as follows:
[0054] (1) Marking effect: A 30×30 mm square area was laser marked on the sample (the laser marking was performed using the TFL-M20 semiconductor-pumped fiber laser marking system produced by Ted Laser, with a laser wavelength of 1064 nm, a laser power of 20 W, a frequency of 40 kHz, and a speed of 1000 mm / s). A colorimeter (UltraScan XE, produced by Hunter Lab, USA) was then used to test the color change of the square marked area. The difference in b value (Δb) before and after laser marking was recorded to characterize the yellowness of the laser mark. The smaller the value, the lower the yellowness of the mark and the better the marking effect.
[0055] (2) Notched impact strength: tested in accordance with ISO 180-2023 standard, with a specimen thickness of 4 mm, cantilever beam notched impact, and notch type A.
[0056] (3) Flame retardant performance: The flame retardant grade of 1.6 mm standard specimens was tested according to UL94 standard.
[0057] Table 3 Properties of ABS compositions in various examples and comparative examples
[0058]
[0059]
[0060] From the data in Table 3, it can be seen that the ABS compositions in Examples 1 to 12 have flame retardancy reaching V-1 level, marking yellowness Δb is less than or equal to 1.2, and notched impact strength is greater than or equal to 25 KJ / m 2 , indicating that the ABS composition of the present invention not only has good flame retardant properties, but also has excellent marking effect and toughness. At the same time, according to Comparative Example 1 and Examples 1 to 3, it can be seen that the mass percentage of butadiene in the ABS resin has an important influence on the laser marking performance and toughness of the ABS composition. When the weight percentage of butadiene in the ABS resin is too small, it is difficult to effectively improve the marking effect and toughness of the ABS composition.
[0061] In addition, according to Example 1, Example 4, Example 5 and Comparative Examples 2 to 4, it can be found that the melt mass flow rate of the PETG resin and the weight percentage of CHDM therein jointly affect the marking effect and toughness of the ABS composition. When the weight percentage of CHDM in the PETG copolyester is too large or too small and the melt mass flow rate of the PETG copolyester is too small, it is difficult to effectively improve the marking effect and toughness of the ABS composition. According to Comparative Examples 5 and 6, it can be further found that in addition to affecting the marking effect and toughness of the ABS composition, the PETG copolyester has a significant promoting effect on the improvement of the flame retardant properties of the ABS composition; when the PETG copolyester is not added, the marking effect, toughness and flame retardant properties of the ABS composition will all decrease, and when the amount of PETG copolyester added is too much, although it can maintain a good marking effect and flame retardant properties, it will cause a significant decrease in toughness.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An ABS composition, characterized in that: By weight, it includes the following components: ABS resin 53-73 parts, PETG copolyester 15-30 parts, brominated flame retardant 11-13 parts, antimony flame retardant 1-3 parts; The weight percentage of butadiene in the ABS resin is ≥20%, and the weight percentage of 1,4-cyclohexanedimethanol in the PETG copolyester is 10% to 30%; The PETG copolyester adopts ISO 1133-1:2011 standard, and the melt mass flow rate at 220° C. and 10 kg is ≥18 g / 10 min.
2. The ABS composition according to claim 1, characterized in that: Among the components of the ABS composition, the weight proportion of ABS resin is 57 to 65 parts, and the weight proportion of PETG copolyester is 20 to 25 parts.
3. The ABS composition according to claim 1, characterized in that: The weight percentage of butadiene in the ABS resin is 22% to 29%.
4. The ABS composition according to claim 1, characterized in that: The melt mass flow rate of the PETG copolyester is 20 to 40 g / 10 min.
5. The ABS composition according to claim 1, characterized in that: The components of the ABS composition also include 0.5 to 1 parts by weight of a processing aid.
6. The ABS composition according to claim 5, characterized in that: The processing aid includes at least one of an anti-drip agent, an antioxidant, and a lubricant.
7. The ABS composition according to any one of claims 1 to 6, characterized in that: The brominated flame retardant includes at least one of brominated triazine and brominated epoxy; And / or, the antimony-based flame retardant includes at least one of antimony oxide and antimonate.
8. The ABS composition according to claim 7, characterized in that: The antimony oxide is antimony trioxide, and the antimonate is sodium antimonate.
9. The method for preparing the ABS composition according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components uniformly and then melting and extruding the components to obtain an ABS composition.
10. Use of the ABS composition according to any one of claims 1 to 8 in preparing plastic casings of household appliances or electronic and electrical products.
Citation Information
Patent Citations
A method for analyzing the content of 1,4-cyclohexanedimethanol unit on the molecular chain of copolyester
CN104569022B
Flame-retardant ABS / PVC / PETG alloy and manufacturing method thereof
CN102807728A
Resin composition for laser marking and sheet for laser marking
JP2020100751A
Flame retarding thermoplastic alloy and its preparation method
US20110095246A1